Edukasi Pencegahan Stunting melalui Penerapan Pola Makan Seimbang pada Desa Tegal Kunir Kidul Mauk Tangerang - winanti, winanti; Sukriyah, Sukriyah; Agistiawati, Eva; Isnaini, Sri Wahyuni; Nuryanti, Yulis; Suseno, Bayu (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2024)
Tegal Kunir Kidul village is one of the areas in Mauk sub-district that still has a high stunting rate among villages in Mauk sub-district. The aim of this activity is to educate the public about preventing stunting through a balanced diet for toddlers. The activity is carried out using a lecture method guided by a moderator. The activity lasted for one day and at the end of the activity a quick division of plants was carried out. Monitoring and evaluation was carried out by asking several participants and all of them expressed satisfaction and enjoyment with this activity. In the future, other, more innovative activities will be carried out with more participants.